Pengaruh Tingkat Pendidikan dan PIA Terhadap Kinerja UMKM (Studi Pada UMKM Rotan) - Rizal Sukma Aliyudin; Robi Maulana Magribi; Siska Nur Alifia (Program Studi Akuntansi Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2023)
The number of MSMEs spread throughout Majalengka and the contribution made by MSMEs to the Majalengka economy is not balanced, this is due to the less than optimal contribution of MSMEs. The lack of MSME contribution is due to the lack of quality of MSME performance. This study aims to empirically prove the influence of education level and the use of accounting information on MSME performance. This study used quantitative research methods. The population of this study was rattan MSME actors in Sindangwangi sub-district and the number of samples used was 75 respondents with sampling techniques using simple random sampling. Data collection techniques in this study using questionnaires and data analysis techniques used are multiple regression analysis techniques using classical assumption tests, hypothesis tests and determination coefficients. The results of this study show that the level of education and the use of accounting information affect performance